2023
DOI: 10.1002/cesm.12011
|View full text |Cite
|
Sign up to set email alerts
|

What did the scientific literature learn from internal company documents in the pharmaceutical industry? A scoping review

Abstract: Objective To identify all scientific papers that used internal industry documents in the pharmaceutical sector and analyze what and how the scientific literature learned about corporate influence in the pharmaceutical sector through these internal documents. Design Scoping review. Methods Using different series of keywords, we searched six databases, PubMed, Scopus, Web of Science, CINAHL, Business Source Complete, and PAIS, for peer‐reviewed journal articles analyzing pharmaceutical corporations' internal doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 68 publications
(281 reference statements)
0
2
0
Order By: Relevance
“…However, concordance was poor (and biased in favor of industry) in meta-analyses when the researchers had financial ties to pharmaceutical firms ( 41 ). Sismundo ( 42 ) refers to the corporate capture of the scientific literature as “ghost-management.” Relatedly, a recent scoping review that examined internal company documents found that industry used “dynamic ghost-management strategies… to safeguard their corporate interest” ( 43 ).…”
Section: Commercial “Research” For the Purpose Of Selling Products Di...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, concordance was poor (and biased in favor of industry) in meta-analyses when the researchers had financial ties to pharmaceutical firms ( 41 ). Sismundo ( 42 ) refers to the corporate capture of the scientific literature as “ghost-management.” Relatedly, a recent scoping review that examined internal company documents found that industry used “dynamic ghost-management strategies… to safeguard their corporate interest” ( 43 ).…”
Section: Commercial “Research” For the Purpose Of Selling Products Di...mentioning
confidence: 99%
“…Sismundo (42) refers to the corporate capture of the scientific literature as "ghost-management. " Relatedly, a recent scoping review that examined internal company documents found that industry used "dynamic ghost-management strategies… to safeguard their corporate interest" (43).…”
Section: Conflicts Of Interest In Depression Research and The Consequ...mentioning
confidence: 99%
“…Pharmaceutical companies invest hundreds of millions of dollars to shape medical science, literature, and physicians' opinions in target treatment areas (1)(2)(3)(4)(5)(6)(7)(8). The contracts they maintain with their various partners-from individual doctors to multimillion-dollar consulting firms and medical publishers-spell out duties and expectations, payments, and procedures.…”
Section: Introductionmentioning
confidence: 99%
“…[9] El desarrollo, elaboración y posicionamiento de nuevos productos y/o servicios farmacéuticos en los mercados implica un conocimiento tanto de las necesidades de salud de los pacientes, como de los actores que integran el sistema sanitario. Se requiere de una intervención integral en la relación médico-paciente-farmacéutico en áreas especializadas de la medicina con el fin de proporcionar el tratamiento más costo/efectivo [10] en el proceso de la prevención y/o recuperación de la enfermedad y en los que puede existir una influencia corporativa [11].…”
Section: Introductionunclassified